2017
DOI: 10.1210/en.2017-00303
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin Stimulates Growth Hormone Release by Utilizing Neuropeptide Y Pathways and Is Dependent on the Presence of Ghrelin in the Ewe

Abstract: Although kisspeptin is the primary stimulator of gonadotropin-releasing hormone secretion and therefore the hypothalamic-pituitary-gonadal axis, recent findings suggest kisspeptin can also regulate additional neuroendocrine processes including release of growth hormone (GH). Here we show that central delivery of kisspeptin causes a robust rise in plasma GH in fasted but not fed sheep. Kisspeptin-induced GH secretion was similar in animals fasted for 24 hours and those fasted for 72 hours, suggesting that the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 88 publications
2
20
0
Order By: Relevance
“…We attempted to clarify the field by utilising specific antagonists to GPR54. In our study, we found no effect of administration of kisspeptin into the LV on GH secretion in intact ewes, which is in agreement with the reported lack of response to peripheral administration in intact cows studies (Whitlock et al 2008) and prepubertal female pigs (Lents et al 2008) but contrasts with a small GH increase reported in ewes (Whitlock et al 2010) although the immediate nutritional status may be key in this model (Foradori et al 2017). In women, both acute and chronic peripheral administration of kisspeptin-54 failed to alter GH concentrations (Jayasena et al 2014).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We attempted to clarify the field by utilising specific antagonists to GPR54. In our study, we found no effect of administration of kisspeptin into the LV on GH secretion in intact ewes, which is in agreement with the reported lack of response to peripheral administration in intact cows studies (Whitlock et al 2008) and prepubertal female pigs (Lents et al 2008) but contrasts with a small GH increase reported in ewes (Whitlock et al 2010) although the immediate nutritional status may be key in this model (Foradori et al 2017). In women, both acute and chronic peripheral administration of kisspeptin-54 failed to alter GH concentrations (Jayasena et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…However, recently published data show kisspeptin can stimulate GH, but only in fasted ewes, by a ghrelin-NPYmediated mechanism (Foradori et al 2017). These complex, and often, contradictory reports may be a result of the large family of RFamide receptors, which can be targeted by kisspeptin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular and cellular regulation of folliculogenesis is complex and not fully understood. NPY is known to regulate female reproductive function through the central neuron system [6]; NPY at the hypothalamus modulates the activity of GnRH neuronal system via NPY1R and NPY2R and regulates LH secretion by the pituitary gland [15][16][17][18][19][20][21]. However, its role in the control of the follicular development at the ovarian level has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the reproductive axis also is regulated by energy balance ( 35 ) and kisspeptin is related to food intake and growth ( 55 , 56 ). Although several recent studies have proposed that kisspeptins regulate reproduction in teleosts, little is known about their role in the control of food intake and energy balance.…”
Section: Discussionmentioning
confidence: 99%